1996
DOI: 10.1074/jbc.271.20.12076
|View full text |Cite
|
Sign up to set email alerts
|

TFII Is Required for Transcription of the Naturally TATA-less but Initiator-containing Vβ Promoter

Abstract: The proximal or core promoter of a typical eukaryotic protein coding gene comprises distinct elements, TATA and/or initiator (Inr). The existence of TATA or Inr at the core promoter suggests that the mechanism of transcription initiation mediated by these two genetic elements may be different. Accordingly, it has been demonstrated that the transcriptional requirements for the TATA-containing, Inr-less ( Transcription initiation of protein coding genes is brought about by RNA polymerase II and a set of general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 29 publications
3
71
0
Order By: Relevance
“…see [29]). A number of studies have identified various proteins as binding at or near the initiator motif, such as RNA polymerase II [3], YY1 [30], E2f(HIP1) [5], TAFII150 [1], USF [6], TFIIA [7], TFII-I [8,9] or TFIID itself [10][11][12], but the actual mechanisms of joint interaction of these proteins with the initiator (binding protein) and TFIID are obscure. The role and form of the TATA box are also more complicated than originally conceived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…see [29]). A number of studies have identified various proteins as binding at or near the initiator motif, such as RNA polymerase II [3], YY1 [30], E2f(HIP1) [5], TAFII150 [1], USF [6], TFIIA [7], TFII-I [8,9] or TFIID itself [10][11][12], but the actual mechanisms of joint interaction of these proteins with the initiator (binding protein) and TFIID are obscure. The role and form of the TATA box are also more complicated than originally conceived.…”
Section: Discussionmentioning
confidence: 99%
“…TAFII28 and RXR ; [2]). In a number of cases there also appears to be specific binding by factors other than TBP to an ' initiator ' motif downstream from the TBP-binding site [3][4][5][6][7][8][9][10][11][12]. There is increasing evidence that particular DNA sequences in the core promoter, other than the TBP-and initiator-binding motifs, play a pivotal role in controlling whether a particular TBP\TAFII complex [13] or other non-TFIID factor (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…TFII-I is a unique transcription factor, because it can function both as a basal factor and as an activator (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Consistent with these functional activities, it has been shown to bind a core promoter element, Inr, and various upstream elements apparently through distinct DNA binding domains (1, 4, 6 -11).…”
mentioning
confidence: 94%
“…In the supershift assay, 2 g of antibody for supershift grade (Santa Cruz Biotechnology) were added before the addition of the 32 P-labeled probe. For immunodepletion, nuclear extracts were treated with 2 g of an antibody against PARP (Upstate Biotechnology) or CD38 (24), or of preimmune serum for 10 min at 0°C before the addition of the probe as described (25).…”
Section: Methodsmentioning
confidence: 99%